2019
DOI: 10.3390/nu11092163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise and Nutritional Intervention on Body Composition, Metabolic Health, and Physical Performance in Adults with Sarcopenic Obesity: A Meta-Analysis

Abstract: People with sarcopenic obesity (SO) are characterized by both low muscle mass (sarcopenia) and high body fat (obesity); they have greater risks of metabolic diseases and physical disability than people with sarcopenia or obesity alone. Exercise and nutrition have been reported to be effective for both obesity and sarcopenia management. Thus, we aimed to investigate the effects of exercise and nutrition on body composition, metabolic health, and physical performance in individuals with SO. Studies investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
150
1
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 49 publications
12
150
1
9
Order By: Relevance
“…Applying exercise intensity peaks in the range corresponding to 60-85% 1RM, high velocity, and RM with intensifying strategies (Gießing, 2008), most determinants responsible for initiating a hypertrophic response (Schoenfeld, 2010) were considered by our protocol. In summary, we observed significant favorable effects on LBM, total and abdominal fat, and lower extremity strength (MILES) that were superior to current studies on sarcopenic/SO cohorts, be it with or without protein supplementation (review in Martinez-Amat et al, 2018;Vlietstra et al, 2018;Hsu et al, 2019). Closest to our study, after 8 months of multiple-set DRT on machines (+whey protein supplementation) applied either two or three times/week, Stec et al (2017) reported LBM changes of 0.4-1.89 kg in older people (60-75 years) with age-related muscle atrophy.…”
Section: Discussionmentioning
confidence: 71%
“…Applying exercise intensity peaks in the range corresponding to 60-85% 1RM, high velocity, and RM with intensifying strategies (Gießing, 2008), most determinants responsible for initiating a hypertrophic response (Schoenfeld, 2010) were considered by our protocol. In summary, we observed significant favorable effects on LBM, total and abdominal fat, and lower extremity strength (MILES) that were superior to current studies on sarcopenic/SO cohorts, be it with or without protein supplementation (review in Martinez-Amat et al, 2018;Vlietstra et al, 2018;Hsu et al, 2019). Closest to our study, after 8 months of multiple-set DRT on machines (+whey protein supplementation) applied either two or three times/week, Stec et al (2017) reported LBM changes of 0.4-1.89 kg in older people (60-75 years) with age-related muscle atrophy.…”
Section: Discussionmentioning
confidence: 71%
“…To our knowledge, this is the first meta-analysis that compares RT plus PS with RT alone or plus placebo supplementation in a healthy elderly population. Notably, there are similar previous studies that compared different populations, such as a younger population [45,46] or elderly hospitalized people [47]; included a combination of other supplements, such as vitamin 3, omega-3, or a dietary intake modification [19,[48][49][50][51]; or studied other outcomes related to body composition [52,53].…”
Section: Discussionmentioning
confidence: 92%
“…As such, nutritional strategies for sarcopenic obesity should target not only an optimal energy intake in order to decrease excess fat mass, but also an optimal nutrient intake in order to increase skeletal muscle mass (60). Recent studies have shown that a combination of a moderate weight loss diet with concurrent exercise (especially resistance exercise) may improve body composition and physical performance in subjects with sarcopenic obesity (61).…”
Section: Discussionmentioning
confidence: 99%